Rama, Ethiopia (Tigray). Routes of Interaction – New Research in the Rama Valley - Pfeiffer, Kristina; Gerlach, Iris (e-Forschungsberichte des DAI, 2020)
The project »Routes of Interaction« is a collaboration between the Sanaa Branch of the Orient-Department, the Department of Earth Sciences – Physical Geography of the Freie Universität Berlin and the Egyptian Museum – Georg Steindorff, Leipzig University. Embedded into the SPP Programme of the DFG »Entangled Africa«, field work has been carried out since 2018. The project investigates various forms of mobility and routes of interaction between the cultures at the northern Horn of Africa and the cultures of the middle Nile River and the northeastern Sudanese Gash Delta. Focusing on the Rama Valley, the survey concentrates on the material evidence for the dimensions of such networks during the 2nd and early 1st millennium BC.